Monitoring the enzymatic oxidation of xenobiotics by hydrogen peroxide through oxidation-reduction potential measurements - Morales Urrea, Diego Alberto (2018)
In this work, three xenobiotics (orange II, phenol, and bisphenol A) were oxidized by hydrogen peroxide in the presence of a horseradish peroxidase (HRP) using a fed-batch system. During the experiments, the oxidation-reduction potential (ORP) of the reaction mixture was measured continuously. Results demonstrate that ORP values only increased when both substrates of the enzyme (hydrogen peroxide and the target compound) were present in the reaction mixture. For all of the tested pollutants, the continuous addition of hydrogen peroxide caused an increase in ORP values. When the reducing substrate was depleted, the addition of an excess of hydrogen peroxide caused a decrease of ORP values. The time at which ORP reached a maximum represented the end of the oxidation process. This maximum could be easily detected by means of the derivative of ORP as a function of time. To extend the application of the developed technique, the enzymatic oxidation of a binary mixture of BPA and OII was also followed using ORP measurements. Results were similar to those observed with only one reducing substrate. This work demonstrates that ORP measurements can be useful to maximize hydrogen peroxide efficiency through the controlled addition of the oxidant during the oxidation of OII, phenol, and BPA catalyzed by HRP. This approach allows a minimization of time and process costs since the reaction end-point can be easily detected on a real-time basis.